Accidente cerebro vascular (ACV) y perfil lipídico en un programa de riesgo cardiovascular de Armenia, Quindío (2022)
Objective: To describe the lipid profile in patients with stroke in a cardiovascular risk program in a first-level health institution in Armenia, Quindío during 2018. Methods: A cross-sectional descriptive study was carried out with a sample of 300 people in a population of a first-level service provider institution with diagnosis or history of stroke. Variables were described in average, standard deviation and confidence intervals, a comparative analysis was made by sex. Variance analysis and square Chi were performed. A relationship of the lipid profile variables with the diagnosis and history of stroke was established. A value of p<0.05 was considered for statistically significant differences. Results: We found a prevalence of stroke in the population at the first level of care of 2.7%, and a statistically significant relationship between the low value of HDL and the antecedent of stroke (p=0.024 value) and the diagnosis of stroke with high TG (p=0.041 value). Conclusions: The literature describes LDL as a factor highly related to the development of LCA, However, the present study found that there is a statistically significant relationship between the diagnosis of LCA with high TG and the history of LCA with low HDL levels, these 2 conditions have been found to be prevalent in this CVR population.